Development of a uric acid biosensor using uricase-immobilized graphene oxide - Omar, Muhamad Nadzmi (2017)
High level of uric acid in the body will cause various diseases for instance gout, Lesch-Nyhan syndrome, cardiovascular and neurological diseases. Currently, the diagnostic applications of uric acid detection are time consuming, lab-based and not practical in terms of continuous monitoring. Therefore, improvements in the accuracy, detection time and sensitivity of these measurements can be done through the use of biosensors. The aim of this study was to develop a fast, high sensitivity and specificity uric acid biosensor through the use of uricase-immobilized graphene oxide. Uricase or urate oxidase was used as a catalyst in the oxidation of uric acid into allantoin and form by-products of hydrogen peroxide and carbon dioxide. The uricase was immobilized onto a carbon-composed platform of graphene oxide (GO). GO is a two-dimensional (2D) single layer of carbon with many active functional groups. GO was used in this study because of its unique properties (large surface area, good biocompatibilityand mechanical flexibility). The GO was synthesized by using a simplified Hummers’ method. Then it was characterized using ultraviolet-visible spectroscopy (UV-Vis), X-ray diffraction (XRD), and field emission electron microscopy (FESEM) and showed a GO with typical characteristics similar to GO formed via other methods of synthesis. Next, uricase was immobilized onto the GO to test the enzyme functionality as a bioreceptor for uric acid detection. EDC-NHS ester was used as a crosslinking reagent to chemically modify the GO. The immobilized uricase showed enzyme activity that was comparable to the free enzyme with 88% activity retained. Again, the modified GO-uricase (GOU) was characterized using FESEM, XRD and energy-dispersive x-ray spectroscopy (EDX). Through FESEM, both modified GO with EDC-NHS and modified GO with immobilized uricase showed a typical FESEM image of GO as reported in the literature. XRD indicated that the uricase may have blocked the peaks of GO and ITO glass due to its large structure. From the EDX data, carbon and oxygen compositions are abundant in the GOU compound along with other molecules for example nitrogen and sodium. Then, the electrocatalytic detection of uric acid (UA) was carried out for the GOU via cyclic voltammetry (CV) using a potentiostat. Hence, the GOU was adhered to a glassy carbon electrode (GCE) to facilitate the redox reaction between the enzyme and the substrate. The electrocatalytic response exhibited a linear dependence on the UA concentration ranging from 0.02 mM to 0.49 mM with a detection limit of 3.45 μM at the signal-to-noise ratio of 3 for CV and 6.37 μM at the signal-to-noise ratio of 3 for chronoamperometry (CA). A selectivity study using ascorbic acid (AA) also was carried out to determine the specificity of the sensor in detecting uric acid even in the presence of other interfering compound. Through the CV, AA did not interfere in the UA detection as it formed its own oxidation peak at 0.15 V whilst oxidation peak for UA at 0.47 V and the oxidation peak of UA is much higher as compared to AA. This indicated that the biosensor was also highly selective towards UA. The biosensor also exhibited a good stability when subjected to stability test using different scan rates. It was able to retain its CV pattern with a distinctive peak of oxidation of UA. Lastly, reproducibility test was carried for the GOU and only 15% reduction of peak current of UA upon observation after 10 days was found. In conclusion, the developed biosensor showed promising results as it was able to detect UA both in uric acid-spiked samples and in the presence of other interfering compound.